2015
DOI: 10.1083/jcb.201502074
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial type III secretion-based protein delivery tool for broad applications in cell biology

Abstract: Protein delivery based on bacterial type III secretion allows controllable injection of bacterial, viral, and human proteins into target cells, functional interaction studies, targeting of proteins to subcellular locations, and systems-level signaling analysis of a given translocated protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 77 publications
(96 reference statements)
0
45
0
2
Order By: Relevance
“…In adult mice, the majority of the splenocytes do not reproduce vigorously, thus transient Cre activities fail to induce recombination effectively in the nongrowth or nondivision somatic cells. These results suggested that as a protein delivery tool, the Bac‐T3SS is suitable for in vivo delivery of transiently functional proteins, opening up the possibility of wide applications such as transcriptional factor delivery for somatic cell reprogramming (Bai et al, ; Bichsel et al, ), tumor antigen for antitumor immunotherapy (Wang et al, ), pathogenic antigen or epitope for anti‐infectious disease vaccines (Russmann et al, ; Rüssmann et al, ), and signaling molecules for intracellular signal transduction (Ittig et al, ). Again, high efficiency, low cost, and ease of manipulation make this protein delivery tool especially attractive for various cellular manipulations for biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In adult mice, the majority of the splenocytes do not reproduce vigorously, thus transient Cre activities fail to induce recombination effectively in the nongrowth or nondivision somatic cells. These results suggested that as a protein delivery tool, the Bac‐T3SS is suitable for in vivo delivery of transiently functional proteins, opening up the possibility of wide applications such as transcriptional factor delivery for somatic cell reprogramming (Bai et al, ; Bichsel et al, ), tumor antigen for antitumor immunotherapy (Wang et al, ), pathogenic antigen or epitope for anti‐infectious disease vaccines (Russmann et al, ; Rüssmann et al, ), and signaling molecules for intracellular signal transduction (Ittig et al, ). Again, high efficiency, low cost, and ease of manipulation make this protein delivery tool especially attractive for various cellular manipulations for biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…At present, transgene techniques, such as transfection of plasmid DNA or messenger RNA (mRNA) by transfection reagents or viral vectors (transduction), are widely used for the expression of functional proteins in mammalian cells (Woltjen et al, ; Zhou & Freed, ). However, these approaches have two main shortcomings: unexpected insertional mutagenesis and enormous overproduction of the target proteins (Ittig et al, ). Transient proteofection offers a safe alternative, however, because most proteins have poor plasma membrane permeability, a strategy for effective transmembrane transport is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cette injection peut s'opérer dans différents types de cellules comme les fibroblastes, les cellules épithéliales et endothéliales ou les lymphocytes T. Ce système est également efficace pour délivrer des effecteurs de type III fonctionnels qui proviennent d'autres bactéries que Y. enterocolitica. Ainsi, nous avons pu observer la déphosphorylation de la MAPK (mitogen-activated protein kinase) p38 induite après stimulation par le TNFα, après l'injection d'OspF, un effecteur de la bactérie S. flexneri qui 2 Une étiquette (tag) constituée des acides aminés EQKLISEEDL, utilisée pour cibler des protéines. C, l'activation de la caspase-3 et les processus terminaux de mort cellulaire par apoptose tels que la condensation de la chromatine et le détachement du substrat, pour les cellules adhérentes.…”
Section: Sécrétion Ou Délivrance Intracellulaire De Protéines Fusionnunclassified
“…Dans un processus infectieux, ces protéines perturbent certains des méca-nismes de signalisation de la cellule hôte afin de détourner des activités cellulaires au profit de la bactérie. Dans un article publié dans le Journal of Cell Biology, nous avons décrit la façon dont nous avons détourné cette nanoseringue bactérienne pour en faire un nouvel outil de délivrance de protéines dans les cellules eucaryotes, et illustré plusieurs applications possibles de cette méthode en biologie cellulaire [2].…”
unclassified